Evaluating Augmented Reality Modules to Enhance Technical Drawing Skills in Indonesian Vocational High Schools - Zuhdi Mizian; Sofyan Sofyan; Saharudin Saharudin (AL-ISHLAH: Jurnal Pendidikan, 2025)
Technical drawing is a core skill in vocational education, particularly in engineering fields where spatial visualization is essential. However, traditional instructional methods often fall short in developing these spatial skills. This study investigates the effectiveness of augmented reality (AR)-based modules in improving engineering drawing comprehension among vocational high school students in Indonesia. A quasi-experimental design was employed with 60 students from two vocational high school classes, divided into an experimental group (AR-based instruction) and a control group (traditional methods). Both groups completed a pre-test and post-test using a validated technical drawing comprehension assessment. The intervention lasted several weeks and included interactive 3D AR content aligned with curriculum standards. The experimental group demonstrated a significant improvement in post-test scores (M = 81.50) compared to their pre-test scores (M = 62.30), representing a 30.8% increase. The control group showed a more modest improvement of 12.2% (M = 61.87 to M = 69.42). Statistical analysis confirmed the effectiveness of the AR modules, with a large effect size (Cohen’s d = 1.78) and significant between-group differences (p 0.001). The findings suggest that AR-based modules substantially enhance spatial understanding and learning outcomes in engineering drawing. These results support the integration of AR technology into vocational education to provide more engaging, effective, and skill-aligned training. Investment in AR infrastructure and teacher training is recommended to maximize educational benefits across similar technical domains.